Peran Profitabilitas Dalam Memediasi Ukuran Perusahaan Dan Modal Kerja Terhadap Nilai Perusahaan Pada Perusahaan Pertambangan - Riyanto, Sugeng; Rinawati, Tri; Kusumawati, Citra Andriani (JURNAL ILMIAH EDUNOMIKA, 2024)
The mining industry is often a very important sector in a country's economy. In Indonesia, the mining sector has a significant contribution to the country's gross domestic product (GDP) and exports. The rich potential of natural resources can encourage companies to openly explore the mining of these resources This research aims to examine the influence of Company Size and Working Capital on Company Value with Profitability as an intervention variable for mining sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This research was conducted using purposive sampling with certain criteria. So the data used was 30 companies for 3 years. The data source used is secondary data. The data collection technique in this research is documentation or library research, namely by collecting all data related to the company's financial reports and then processing it using the SmartPLS application. The results of this research prove that company size has a significant positive effect on profitability, working capital has no effect on profitability, company size has a significant positive effect on company value, working capital has a significant positive effect on company value, profitability is able to mediate the effect of company size on company value, profitability Unable to mediate the effect of Working Capital on Company Value, Profitability has a Significant Positive effect on Company Value.